Library consortia contributing to college affordability: collection and OER initiatives in the Consortium of Academic and Research Libraries in Illinois. Issue 3 (17th July 2020) - Sweet, Christopher; Clarage, Elizabeth C.
Abstract : Purpose: The Consortium of Academic and Research Libraries in Illinois (CARLI) consists of 128 libraries. This paper aims to present an analysis of collection and open educational resources (OER) initiatives undertaken by CARLI over the past decade that contribute to improving college affordability. Design/methodology/approach: After reviewing important literature pertaining to library consortia and college affordability, this paper presents a detailed case study of CARLI's collection and OER initiatives. Findings: Owing to their economies of scale, library consortia have the potential to make substantial contributions to improving college affordability. Originality/value: Compared to the efforts of individual libraries to improve college affordability, library consortium efforts have received far less attention in the professional literature. The work of the CARLI consortium documented here can provide a template for other library consortia that are working to improve college affordability.